CRHR1 mediates the transcriptional expression of pituitary hormones and their receptors under hypoxia - Wang, Tong Ying; Xia, Fang Yuan; Gong, Jing Wen; Xu, Xiao Kang; Lv, Min Chao; Chatoo, Mahanand; Shamsi, Bilal Haider; Zhang, Meng Chen; Liu, Qian Ru; Liu, Tian Xing; Zhang, Dan Dan; Lu, Xin Jiang; et al. (Frontiers in Endocrinology, 2022)
Hypothalamus-pituitary-adrenal (HPA) axis plays critical roles in stress responses under challenging conditions such as hypoxia, via regulating gene expression and integrating activities of hypothalamus-pituitary-targets cells. However, the transcriptional regulatory mechanisms and signaling pathways of hypoxic stress in the pituitary remain to be defined. Here, we report that hypoxia induced dynamic changes in the transcription factors, hormones, and their receptors in the adult rat pituitary. Hypoxia-inducible factors (HIFs), oxidative phosphorylation, and cAMP signaling pathways were all differentially enriched in genes induced by hypoxic stress. In the pituitary gene network, hypoxia activated c-Fos, HIFs with specific pituitary transcription factors (Prop1), targeting the promoters of hormones and their receptors. HIF and its related signaling pathways were significantly elevated and can be a promising biomarker during acute or constant hypoxia. Hypoxia stimulated the transcription of marker genes for microglia, chemokines, and cytokine receptors for the inflammatory response. Corticotropin-releasing hormone receptor 1 (CRHR1) mediated the transcription of Pomc, Sstr2 and Hif2ɑ, and regulated the function of HPA axis. Together with Hif, c-Fos initiated and modulated dynamic changes in the transcription of hormones and receptors. Their receptors were also implicated in the regulation of functions of target cells in the pituitary network under hypoxic stress. CRHR1 played an integrative role in the hypothalamus-pituitary-target axes. This study provides new evidence for CRHR1 involved changes of hormones, receptors, signaling molecules and pathways in the pituitary induced by hypoxia.